AKOMODASI PESANTREN PADA KESENIAN RAKYAT DI CANGKRINGAN, SLEMAN, YOGYAKARTA - Kholid Mawardi (IBDA` : Jurnal Kajian Islam dan Budaya, 2017)
This study investigated the construction of thoughts by KH. Ahmad Masrur and al-Qodir Islamic Boarding School to accomodate folk art; to reveal the relationship among KH. Ahmad Masrur, al-Qodir Islamic Boarding School, and folk art communities in Wukirsari village; and to find out the approaches of accommodation implemented in the folk art Village. The findings of this study led to some conclusions. First, on the one hand, Mr. Masrur (an Islamic expert) wanted to send the goodness and the beauty of Islam not only to be achieved by Moslems but also by other religious community. On the other hand, the folk art community wanted to maintain their existence in the diverse society. Therefore, those two intentions are linked to each other in order to accomplish those goals. Second, the relationship among Mr. Masrur, al-Qodir Islamic Boarding School, and Wukirsari village folk art community; in terms of historical context, it was the repetition of the relationship pattern in the past time that occured during the Islamisation process in Java. It was carried out by placing the locality as the basis of Islam. Mr. Masrur, al-Qodir Islamic Boarding School put themselves as the exponents of folk art; Mr. Masrur had the role as the patron and the community folk art had the role as the clients, and the overall relationship was accomplished based on mutually beneficial relationship. Third, the forms of accommodation roposed by Mr. Masrur towards folk art in Wukirsari village were through compromise and tolerance. The form of the compromise was visible through the willingness of both parties to feel and understand the circumstances of one to each other party. As for the form of tolerance, it was implemented by Mr. Masrur and al-Qodir Islamic Boarding School deliberately to avoid various disputes and conflicts.